International Expansion of United States Franchisors: A Status Report and Propositions for Future Research. Issue 4 (1st October 2016) - Hoffman, Richard C.; Watson, Sharon; Preble, John F.
Abstract : Given the growth of franchising globally, now is an important time to consider the international expansion trends of franchisors. This study examines current trends in the international expansion plans of United States franchisors using a unique data set drawn from 438 announcements on the International Franchise Association's website made by 85 franchisors over nine years. The findings describe the scope, duration, markets, entry modes used, and expansion rationale. Contrary to past practices, United States franchisors are more focused on expanding into the emerging markets of Asia rather than the developed markets of the West. It appears that they are attracted by the growth in these markets. Finally, the results are used to summarize the key trends in international franchise expansion and to generate propositions for future research. Some limitations and implications for practice are discussed.